CONVERGENCE ANALYSIS AND SPATIAL RELATIONSHIP OF ECONOMIC GROWTH BETWEEN DISTRICT/CITY IN SOUTH SULAWESI PROVINCE - Rahmat Arapi; Baso Amang; Abbas Selong (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Decrease in the gap (convergence) of economic growth between regencies/cities in the province of South Sulawesi; (2) identify the spatial relationship of economic growth between regencies/cities in South Sulawesi Province. This study uses secondary data sourced from the Central Statistics Agency of South Sulawesi Province. The research subjects were 24 consisting of 21 regencies and 3 municipalities with a time span of 2011-2021. Convergence was analyzed using the Eviews 11 program, while the spatial linkage was analyzed using the Geoda program. The results showed that: (1) there was a divergence of economic growth based on the analysis of sigma convergence and beta convergence, as well as the addition of control variables in the form of HDI and PMTB in the conditional beta convergence test which also failed to show a decrease in income dispersion between districts/cities in South Sulawesi Province; (2) there is a significant spatial relationship between economic growth in Maros Regency, Takalar Regency, Pinrang Regency, and Luwu Regency based on testing using LISA Cluster Map and Moran's I Scatterplot.